Customers satisfaction towards two and three star hotels in the state of Terengganu / Zainuddin Zakaria and Abdul Kadir Othman - Zakaria, Zainuddin; Othman, Abdul Kadir (2003)
Various researches have been conducted on the tourist industry in Malaysia specifically on strategies and methods of attracting tourists to visit a particular destination. However, there are limited studies done on the perceptions of customers on hotel services especially in the state of Terengganu. This study tries to identify the perception of present and past guests towards two and three star hotels in the state. Four, two-star hotels and three, three-star hotels in the state have been identified. The research data were gathered through the self-administered interviews with two types of respondents; i.e. the customers and the management staff of the hotels under study. More than three hundred present and past guests of the two and three star hotels in the state in addition to more than thirty members of the management staff have been interviewed. The responses were analysed based on the SERVQUAL model introduced by Parasuraman, Zeithaml and Berry in 1988. Therefore, the results show the expectations of customers before and the perceptions of the customers after receiving the services for at least a one-night stay at the hotels. The results were compared with the perceptions of the management staff on the expectations of customers of the hotels under study. The gap between customer's expectation and their actual experience of staying in the hotels identified was analysed. In addition, any gap between management perceptions of customers’ expectation and customers’ own experiences was also looked into. Two nonrated hotels that includes UiTM hotel in Dungun were included in the study to compare and contrast the services they offered with the two and three star hotels.